Dynamics of Muslimat Nahdlatul Ulama Under Mahmudah Mawardi Leadership In 1950-1979 - Samsuniyah Samsuniyah (Journal of Nahdlatul Ulama Studies, 2021)
This research discussed about Muslimat Nahdlatul Ulama (Muslimat NU) in 1950-1979 AD led by Mahmudah Mawardi. Muslimat NU at that time experienced a significant development than before. This article starts the discussion by providing the condition of Muslimat Nahdlatul Ulama before the leadership of Mahmudah Mawardi, which were Chadidjah Dahlan period in 1946-1947 and Hindun period 1947-1950. Among the superior work program by Muslimat NU at that time was the eradication of illiteracy. In the social field, Muslimat NU established Muslimat NU Welfare Foundation that specifically handled Muslimat NU programs engaged in social affairs. When the government issued the Family Planning (KB) program, Muslimat NU gave a positive and active response in succeeding the program. In the field of politics, Muslimat NU participated in the struggle for the law on marriage that does not violate Islamic sharia and purposing to protect women. The results of this study explain that the Muslimat NU during Mahmudah Mawardi's leadership experienced rapid progress, this was supported by its members in developing the organization and the support of PBNU as its core organization.